Advancement On The Use Of Organic Waste Into Organic Materials That Are Good For Plants - Lutfi Henderlan Harahap (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service activity focuses on providing education on the importance of processing organic waste into beneficial organic materials for plants to preserve the environment. This initiative not only supports agriculture and the local economy but also contributes to environmental conservation by reducing waste disposal and incineration. The outcome is that the counseling on processing organic waste into useful organic materials for plants at Gajah Mada High School proceeded smoothly. The students at Gajah Mada High School showed great enthusiasm in participating in the community service activities. This educational activity serves as a means to enhance students' knowledge about processing organic waste into beneficial organic materials for plants, thus, it is hoped that they can implement organic waste processing both in their surroundings and at school.